A comparative study of peripheral and non-peripheral zinc (II) phthalocyanines incorporated into mesoporous silica nanoparticles - López Zeballos, Noelia del Carmen (2015)
The properties of two new lipophilic isomeric phthalocyanines 2,9(10),16(17),23(24)-tetrakis-[(2-dimethylamino)ethylsulfanyl] phthalocyaninatozinc(II) (Pc9) and 1,8(11),15(18),22(25)-tetrakis[(2- dimethylamino)ethylsulfanyl]phthalocyaninatozinc(II) (Pc10), incorporated into mesoporous silica nanoparticles were investigated. The photophysical studies showed that these dyes had a lower aggregation when incorporated into mesoporous silica nanoparticles than when incorporated into other carriers. Both systems were able to generate singlet oxygen, although with values lower than those obtained in homogeneous media, suggesting that a small portion of the phthalocynines was incorporated in an aggregated form. The incorporation efficiency determined by UV-Vis spectroscopy exceeded 99%. A higher core release was obtained for the non-peripheral isomer (Pc10). This could be attributed to the steric hindrance effect of the substituents as compared with the peripheral substituted isomer (Pc9). © 2014 Elsevier Ltd. All rights reserved.